1978
DOI: 10.1002/jbm.820120503
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of hydrolyzed polyacrylonitrile

Abstract: Measurements of the permeability coefficients of various compounds up-to a molecular weight of about 70,000 have shown clearly that membranes prepared from hydrolyzed polyacrylonitrile are about 10 times more permeable than those made of poly(2-hydroxyethyl) methacrylate. The higher permeability is probably due more to the higher water content (about 75%) than to the type of network. The high mechanical strength of the membranes and their good permeability to compounds possessing a comparatively high molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The transport properties of different solutes in HEMAbased hydrogels have been studied by measuring the permeability of membranes prepared from the copolymers. [30][31][32][33] The determination of the diffusion coefficients from these measurements is complicated by the need to determine independently the partition coefficients of the diffusant for the system membranesolvent; such information has been obtained only for inorganic salts. The main conclusions derived from such studies are the increased permeability with increasing water content in the gels and with decreasing degree of cross-linking and the higher permeability of inorganic salts across ampholytic membranes (that contain the same amounts of weak acidic and weak basic groups) compared with neutral membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The transport properties of different solutes in HEMAbased hydrogels have been studied by measuring the permeability of membranes prepared from the copolymers. [30][31][32][33] The determination of the diffusion coefficients from these measurements is complicated by the need to determine independently the partition coefficients of the diffusant for the system membranesolvent; such information has been obtained only for inorganic salts. The main conclusions derived from such studies are the increased permeability with increasing water content in the gels and with decreasing degree of cross-linking and the higher permeability of inorganic salts across ampholytic membranes (that contain the same amounts of weak acidic and weak basic groups) compared with neutral membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Beside its scientific interest, this conclusion appears to have some practical significance. Indeed, acidic PAN hydrolysis at low temperatures by action of HNO 3 6 or a H 2 SO 4 /H 3 PO 4 mixture 16 is the only method to prepareAN−AAm multiblock copolymers testified for various applications. , Note that 13 C NMR spectrometry gives the valuable but limited set of the HPAN structure parameters. Meanwhile, the theory of the neighboring group effect enables one to calculate any parameter of the reaction product structure as soon as the rate constants k 0 , k 1 , and k 2 are estimated .…”
Section: Resultsmentioning
confidence: 99%
“…2 On the contrary, PAN hydrolysis by concentrated acids at 15-50 °C leads to the formation of a AN-AAm copolymer, sometimes containing also small amounts of acrylic acid groups. [6][7][8][9][10][11] At elevated temperature (110 °C), AAm groups cyclization occurs with formation of glutarimide (GI) cycles. 10,11 (GI cycles were never observed in the products of alkaline PAN hydrolysis because of their extreme instability in an alkaline medium as shown by Sawant and Morawetz.…”
Section: Introductionmentioning
confidence: 99%
“…In one of papers from our Institute e.g. (58),it was shown that compounds with molecular weight up to 64 030 may pass through membranes of hydrolyzed polyacrylonitrile with the water content 7 4 wt.%.…”
Section: B) Mutual Interaction Between Soluble Compounds Of Naturalmentioning
confidence: 99%